1975
DOI: 10.1002/star.19750270705
|View full text |Cite
|
Sign up to set email alerts
|

Sweetzyme — A New Immobilized Glucose Isomerase

Abstract: The enzymatic isomerization of glacose to fructose is attracting significant attention f r o m scientific as well as industrial quarters. In recent years, high fructose syrups ("isosyrups") produced b y enzymatic isomerization of high DE-syrups have been introduced successfully, primarily i n the U.S.A.A decisive factor for the ability of isosyrups t o compete is enzyme costs. T h e development of immobilized glucose isomerase makes multiple use of the enzyme possible and thus makes the econom y of the isomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…On this basis, the results obtained here were compared with those reported by others as follows: Among the bacterial genera reported to have glucose-isomerizing activity, E'scheriehia (NATAKE and YOSIIIMURA 1963, YAMANAKA 1965, Aerobacter (TSUMURA Enzymes of glucose isomerization and SATO 1960, NATAKE and YOSHIMURA 1963, MURAYAMA and SHIROO 1964, SHICH et al 1974), Brevibacterium (NATAKE and YOSHIMURA 1963, ICHIMURA et al 19651, Micrococcus (NATAKE and YOSHIMURA 1963, Leuconostoc (YAMANAKA 1960), Lactobacillus (NATAKE and YOSHIMURA 1963, YAMANAKA 1960), Bacillus (TAKASAKI and TANABE 1962, YOSHIMURA et a2. 1966, NAKAYAMA 1969, LOUIS et a2.1972, ZITTAN et al 1975, SUEKANE et al 1978, were also observed to have glucose-isomerizing activity in the present experiments. As for Arthrobacter (LEE et al 1972) (MARHALL and KOOI 1957).…”
Section: Discussionsupporting
confidence: 69%
“…On this basis, the results obtained here were compared with those reported by others as follows: Among the bacterial genera reported to have glucose-isomerizing activity, E'scheriehia (NATAKE and YOSIIIMURA 1963, YAMANAKA 1965, Aerobacter (TSUMURA Enzymes of glucose isomerization and SATO 1960, NATAKE and YOSHIMURA 1963, MURAYAMA and SHIROO 1964, SHICH et al 1974), Brevibacterium (NATAKE and YOSHIMURA 1963, ICHIMURA et al 19651, Micrococcus (NATAKE and YOSHIMURA 1963, Leuconostoc (YAMANAKA 1960), Lactobacillus (NATAKE and YOSHIMURA 1963, YAMANAKA 1960), Bacillus (TAKASAKI and TANABE 1962, YOSHIMURA et a2. 1966, NAKAYAMA 1969, LOUIS et a2.1972, ZITTAN et al 1975, SUEKANE et al 1978, were also observed to have glucose-isomerizing activity in the present experiments. As for Arthrobacter (LEE et al 1972) (MARHALL and KOOI 1957).…”
Section: Discussionsupporting
confidence: 69%
“…Alternative procedures include freezing the crosslinked precipitate prior to drying, allowing the centrifuged cells to autolyse before crosslinking, and then flocculating and drying or disrupting the cells and then flocculating and crosslinking the homogenate. The immobilized enzyme is then used in column reactors at (Zittan, 1975;Amotz et al, 1976;Hemmingsen, 1979). …”
Section: Fermentation and Production Of Glucose Isomerasementioning
confidence: 99%
“…At the same time, a group at Novo lndustri A/S succeeded in producing an immobilized glucose isomerase product (Zittan~Poulsen and Hemmingsen, 1975;) which could compete economically, could be used without the addition of cobalt, and could withstand the pressure in the large industrial fixed..bed reactors where heights of 7 m are not unusuaL…”
Section: Immobilized Glucose Isomerasementioning
confidence: 99%